Algorithm of the Investigator's and Body of Inquiry's Actions in Investigation of Cellular Frauds - Leila Y. Aksenova (Сибирское юридическое обозрение)
Taking into account specific features of objective nature of the studied acts the author proves that it is necessary to make an algorithm of the investigator's and interrogation unit activities in investigation of cellular frauds. The literature revised, investigations of this category of cases enable the author to identify the most typical mistakes in activity of the specified subjects of law enforcement agencies and formulate the algorithm of investigative and other procedural actions performed for detection and investigation of cellular frauds.